Are Family and Nonfamily Tourism Businesses Different? An Examination of the Entrepreneurial Self-Efficacy–Entrepreneurial Performance Relationship. (August 2014) - Hallak, Rob; Assaker, Guy; O'Connor, Peter
Drawing on literature on tourism, entrepreneurship, and family businesses, this research uses a structural model to examine the relationship between entrepreneurial self-efficacy (ESE) and enterprise performance. Based on samples of family-owned (N = 158) and nonfamily-owned (N = 143) small- and medium-sized tourism enterprise owners in regional South Australia, confirmatory factor analysis, structural equation modeling, and multigroup invariance tests were used to validate the proposed structural model where ESE is the exogenous variable and performance is the endogenous variable. The study also examined if the causal model was invariant (equivalent) between family and nonfamily entrepreneurs to identify key differences between these two groups. Results support the validity of the models, with tourism business owners' ESE having a significant positive effect on enterprise performance. The results of the multigroup invariance tests also indicated that the measurement models, structural model, and residual structure were equal across family and nonfamily business owners. Although previous studies have suggested differences between family- and nonfamily-owned businesses with regard to pattern of ownership, governance, management and succession, business structure, goals, and strategies, this study found that the "entrepreneurial self-efficacy" of business owners (regardless of whether or not the business is family owned) is an important predictor of business performance. The findings suggest that destination managers and policy makers need to support the ESE of local tourism business owners if they wish to enhance performance within the industry and the destination.